Pengaruh Kualitas Produk, Citra Merek, Dan Harga Terhadap Keputusan Pembelian Pada Produk Jersey Iyog ( Studi pada Atlet Bola Voli Kota Pasuruan ) - Islamiyah, Haiza; Salim, Muhammad Agus; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study was to determine how the influence of Product Quality, Brand Image and Price on Purchasing Decisions. The population in this study were Pasuruan City Volleyball Athletes. The Non-Probability Sampling method is purposive sampling with a sample of 70 respondents. The data was processed using SPSS with the results of the study simultaneously showing that it had a simultaneous effect on purchasing decisions, and partially there were: 1) There was a positive and significant influence of Product Quality on Purchase Decisions for Iyog Jersey products 2) There was no significant influence of Brand Image on Purchase Decisions for Iyog Jersey Products 3) There was a positive and significant influence of Price on Purchase Decisions for Iyog Jerseys. Keywords: Product Quality, Brand Image, Price, Purchasing Decision